Empirical analysis of R&D spending, transport infrastructure development and CO2 emissions in China - Han, Ling Mei; You, Jian Qiang; Meng, Jie Ning; Fu, Yu Long; Wu, Song Ling (Frontiers in Environmental Science, 2023)
Over the past few decades, the transportation sector has been the largest contributor to CO2 emissions in China. Research and Development spending leads to technological innovation in the country and could affect the CO2 emission in the country. Therefore, this study analyzes the nexus between CO2 emissions, transport infrastructure and R&D spending in China. A QARDL approach was used for the data analysis, which revealed Research and Development and Transport infrastructure has a positive impact on CO2 emissions. R&D was only significant in the first 25% quantile, while transportation was significant in almost all quantiles. These results suggest that R&D spending in China is mainly allocated to the sectors that emit the CO2 emission. It is recommended that government should allocate more R&D to carbon-reducing sectors. Furthermore, the government should consider green transportation investments and renewable energy projects in the transportation sector to reduce CO2 emissions in the country.